Hydrogen isotopic composition of CI- and CM-like clasts from meteorite breccias – Sampling unknown sources of carbonaceous chondrite materials. (1st March 2020) - Patzek, Markus; Hoppe, Peter; Bischoff, Addi; Visser, Robbin; John, Timm
Abstract: Volatile-rich, CI- and CM-like clasts occur in different brecciated achondrite and chondrite groups. The CI-like clasts in HEDs, polymict ureilites, as well as ordinary, CR, and CB chondrites have a similar mineralogy, indicating a similar alteration history. However, when viewed in detail, their mineral chemistry shows some minor differences between the clasts from different meteorite groups. For CM-like clasts found in HED meteorites, the clasts are, based on their mineralogy, clearly fragments of CM chondrites. To be able to decipher whether CI- (or CM-)like clasts from different meteorite groups are related to certain meteorite classes known to contain volatiles, we obtained D/H ratios of several clasts from the meteorite groups mentioned above and compared them with those of CI and CM chondrites as well as to unique carbonaceous chondrites such as Bells, Essebi, and Tagish Lake. Considering the δD-values, CM-like clasts in HEDs span a similar range compared to bulk values of CM chondrites, further indicating that CM-like clasts are fragments of CM chondrites. For CI-like clasts a clear distinction can be made: While CI-like clasts in HEDs and ordinary chondrites show a very similar range in their δD-signatures compared to "common" CI chondrites, meaning that these clasts are likely related to CI chondrites, the CI-like clasts in polymict ureilites are enriched in D up to 3000‰; a similarly high enrichment is found for the CI-like clasts in CR chondrites. Thus, although the CI-like clasts in ureilites and CR chondrites likely experienced similar alteration histories as the CI-like clasts found in the other meteorite types, these clasts probably formed in a different region than the CI chondrites and, thus, are more accurately referred to as C1 clasts. Overall, the existence and isotopic signatures of the C1 clasts in several meteorite groups proves the existence of additional primitive, volatile-rich material in the (early) Solar System besides the matter we study as the CI, CM, and CR chondrites. This material was distributed throughout the Solar System very early and might have played an important role for the volatile inventory of the terrestrial planets.